2003
DOI: 10.1152/jn.00280.2003
|View full text |Cite
|
Sign up to set email alerts
|

Vasoactive Intestinal Peptide Selectively Depolarizes Thalamic Relay Neurons and Attenuates Intrathalamic Rhythmic Activity

Abstract: Lee, Sang-Hun and Charles L. Cox. Vasoactive intestinal peptide selectively depolarizes thalamic relay neurons and attenuates intrathalamic rhythmic activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
17
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 63 publications
(94 reference statements)
3
17
1
Order By: Relevance
“…In addition, it was reported that VIP and PACAP modulate the depolarizations of the thalamocortical projection neurons by affecting the activities of the hyperpolarization activated cationic currents (Sun et al, 2003) and that VIP attenuates the slow (2-4-Hz) intrathalamic rhythmic activities by shifting the membrane potential of the relay neurons to decrease the probability of burst discharge (Lee and Cox, 2003). However, there is little information about the functional significance of these effects or which receptor mediates these effects.…”
Section: Functional Implications Of the Localization Of Vip/pacap Recmentioning
confidence: 99%
“…In addition, it was reported that VIP and PACAP modulate the depolarizations of the thalamocortical projection neurons by affecting the activities of the hyperpolarization activated cationic currents (Sun et al, 2003) and that VIP attenuates the slow (2-4-Hz) intrathalamic rhythmic activities by shifting the membrane potential of the relay neurons to decrease the probability of burst discharge (Lee and Cox, 2003). However, there is little information about the functional significance of these effects or which receptor mediates these effects.…”
Section: Functional Implications Of the Localization Of Vip/pacap Recmentioning
confidence: 99%
“…In addition to classic neurotransmitters, peptides also play an important role in controlling the firing mode of thalamic neurons. These peptides include cholecystokinin (Cox et al, 1995(Cox et al, , 1997Lee and McCormick, 1997), neuropeptide Y (Sun et al, 2001a,b), somatostatin (Leresche et al, 2000;Sun et al, 2002), nociceptin (Meis et al, 2002), pituitary adenylate cyclase-activated peptide, and vasoactive intestinal peptide (Lee and Cox, 2003;Sun et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…These neuropeptides have pronounced effects on the central nervous system as well as on neurons and effector targets of the autonomic nervous system. For example, in the central nervous system, PACAP is involved in hippocampal synaptic plasticity and associative learning in mice (5), whereas VIP has been shown to regulate intrathalamic rhythm activity and may modulate information transfer through the thalamocortical circuit (6). In the peripheral nervous system, PACAP and VIP appear to play a major role in autonomic regulation of the cardiovascular system.…”
mentioning
confidence: 99%